Atrial Fibrillation: from the guidelines to the reality - Costa Reis, Patrícia (2006)
Background: Atrial Fibrillation (AF) is a very frequent arrhythmia. A devastating consequence of AF is stroke and 15% of all strokes are caused by AF. Several trials have proved a significant reduction in the risk of stroke with anticoagulation (AC). New guidelines have suggested AC for at least three weeks after cardioversion and long term AC for patients older than 75 years with AF, as well as those with risk factors for a thromboembolic event. Long-term AC in the community is safe and effective, even in the elderly. However, some physicians avoid prescribing AC.Objectives: Determine the prevalence of AF in patients attending the Internal Medicine Department of Fernando Fonseca Hospital, over the last 9 years; study the prevalence of stroke in these patients; determine the use of AC at discharge of patients with AF in 2004.Design: retrospective, event driven clinical database analysis.Results: In 9 years AF was found in 6.7% (927/13800) of patients. In 2004, 122 patients with AF were hospitalised and 17.2% had cerebrovascular disease. AC on discharge was noted in only 22.2% of these patients. Conclusions: Even though it has been proved that AC reduces the risk of stroke in patients with AF, in general practice the number of patients anticoagulated is small. We must change this attitude in order to reduce the morbility and mortality associated to stroke, the leading cause of death in our country.